Lesson Study: Upaya Peningkatan Kualitas Pembelajaran dan Kolegialitas Guru - Sri Wahyuni; Dwi Rukmini; Sri Wuli Fitriati; Ervina Juli Aryani; Glendia Fisca (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2021)
Minimum exposure on the lesson study practices for English teachers of Junior High Schools in Sub Rayon (SR)12 Semarang led to the formulation of this lesson study training. The purpose of this training was to develop the teachers’ professionalism which was expected to be reflected in the learning quality. This program aimed at improving the teachers’ understanding on the concept, advantages, stages and implementation model of lesson study. Besides, the training was expected to provide the English teachers with practical experiences about how to implement lesson study in real teaching and learning activities. The training involved 26 English teachers of Junior High Schools of SR 12 Semarang and four student English teachers of Universitas Negeri Semarang.  The lesson study training was delivered in the forms of presentation of conceptual materials and lesson study practices. The findings show that the English teachers obtain more knowledge of the concept, advantages, stages, and implementation model of lesson study. In addition, they opine that lesson study can improve their professional competence in general and learning quality in particular. It is expected that this will be sustainable program that can reach wider audience. Terbatasnya pelatihan lesson study bagi guru MGMP Bahasa Inggris SMP Sub Rayon (SR) 12 Kota Semarang mendorong adanya program pelatihan lesson study. Tujuan pelatihan lesson study adalah untuk meningkatkan profesionalisme guru yang diharapkan dapat tercermin pada kualitas pembelajaran. Program ini bertujuan untuk meningkatkan pemahaman guru mengenai konsep, manfaat, tahap, dan model implementasi lesson study. Selain itu, pelatihan ini diharapkan memberikan pengalaman praktis bagaimana Lesson Study diimplementasikan dalam pembelajaran. Program ini melibatkan 26 guru Bahasa Inggris SMP SR 12 Kota Semarang dan empat mahasiswa praktikan PPL Universitas Negeri Semarang. Program pelatihan lesson study dilaksanakan dalam bentuk penyampaian teori mengenai lesson study dan pelaksanaan praktek lesson study. Target program ini adalah guru mampu menjelaskan berbagai konsep terkait lesson study serta dapat mengimplementasikannya bersama komunitas guru pada lingkungan sekolah masing-masing. Setelah mengikuti pelatihan lesson study, guru mengetahui konsep, manfaat, tahapan dan model implementasi lesson study. Selain itu, para  guru berpendapat bahwa pelatihan lesson study dapat meningkatkan kompetensi professional secara umum dan kualitas pembelajaran secara khusus. Diharapkan bahwa pelatihan semacam ini akan berkelanjutan dan menjangkau lebih banyak khalayak sasaran.